PENGGUNAAN TECHNOLOGY ACCEPTANCE MODEL UNTUK MENGUKUR PENERIMAAN LAYANAN MOBILE THIRD GENERATION (3G) DI KOTA PALEMBANG - HERI SETIAWAN (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This study aimed to measuring the third generation mobile services (3G) receive using the Technology Acceptance Model. This study uses data collected through a survey of user mobile services provider of Telkomsel, Indosat and XL in Palembang. Sampling method in this study using Purposive Sampling with a sample of 180 respondents. Data analysis using SPSS for Windows version 20.00 with Linear Regression Analysis method. The independent variables were perceived usefulness, ease of use, perceived enjoyment, attitude of use and the dependent variable is the behavioral intention. The results showed that perceived usefulness, ease of use, perceived enjoyment, attitude of use simultaneously have a significant effect on behavioral intention. Perceived usefulness have significant effect on behavioral intention. Perceived ease of use significantly influence on behavioral intention. Perceived enjoyment have significantly effect on behavioral intention. Attitude have significant effect on behavioral intention. Consideration of the factors identified should lead to more successful adoption of 3G. The study implies that the 3G mobile telecommunication companies need to lift consumers’ intention to adopt 3G mobile services. Users’ of 3G mobile services need to be provided with more diverse and entertaining ways of communicating, which are at the same time easily accessible and convenient to use. The paper enhance understanding of user acceptance of 3G mobile communication services.